Triathletes are over-represented in a population of patients with ALS. Issue 7 (December 2014) - Gotkine, Marc; Friedlander, Yechiel; Hochner, Hagit
Abstract The nature of the association between vigorous physical activity and ALS is unknown, although a possible link to head and neck trauma has been suggested. Observation of a prize-winning triathlete who developed ALS prompted us to analyse our ALS clinic data. We undertook a retrospective cross-sectional clinic-based observational study, analysing self-reported patient data from 185 patients with ALS enrolled in our ALS clinic. We identified patients reporting regular participation in triathlons (ALS-T) and compared clinical and demographic data to other patients with ALS. Data from the Israeli Triathlon Association were used to estimate the frequency of triathlon participation in the general population. Of 185 patients with ALS, five (2.7%) reported triathlon participation compared to the estimated exposure rate of 0.17% in the general population, giving an odds ratio of 16.15 (95% CI 5.85–36.38, p < 0.0001); this highly significant odds ratio remained even after adjustments were made to address potential sources of bias. ALS-T were younger and had a higher frequency of bulbar onset compared to other patients with ALS. In conclusion, our observed excess of triathletes in ALS patients justifies a cohort study focusing on triathletes and suggests that vigorous exercise itself may be related to a predominance of bulbar-onset patients, irrespective of head and neck trauma.